2018
DOI: 10.1534/g3.117.300170
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Tissue Atlas of the Malaria Mosquito Anopheles gambiae

Abstract: Anopheles gambiae mosquitoes transmit the human malaria parasite Plasmodium falciparum, which causes the majority of fatal malaria cases worldwide. The hematophagous lifestyle defines mosquito reproductive biology and is exploited by P. falciparum for its own sexual reproduction and transmission. The two main phases of the mosquito reproductive cycle, previtellogenic (PV) and postblood meal (PBM), shape its capacity to transmit malaria. Transition between these phases is tightly coordinated to ensure homeostas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 67 publications
4
38
0
Order By: Relevance
“…The same signals induce expression of negative regulators, including miR-276, that warrant the timely reset of the fat body metabolism (Bryant et al, 2011;Lampe and Levashina, 2018;Mane-Padros et al, 2012b). Massive degradation of AAs in the fat body supports high energy demands of nutrient mobilization and protein synthesis for successful egg development (Fuchs et al, 2014b;Zhou et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same signals induce expression of negative regulators, including miR-276, that warrant the timely reset of the fat body metabolism (Bryant et al, 2011;Lampe and Levashina, 2018;Mane-Padros et al, 2012b). Massive degradation of AAs in the fat body supports high energy demands of nutrient mobilization and protein synthesis for successful egg development (Fuchs et al, 2014b;Zhou et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…However, how the miRNAs that regulate mosquito metabolism impact vector-parasite interactions is unknown. In A. gambiae, a major malaria vector in sub-Saharan Africa, blood feeding increases the fat body levels of miR-276-5p transcripts (miR-276 hereafter) during the mid-/late-phase of the reproductive cycle (Lampe and Levashina, 2018). Here, we report that miR-276 tunes the duration of the reproductive cycle by inhibiting expression of the branched chain amino acid transferase in the fat body.…”
Section: Introductionmentioning
confidence: 89%
“…quinquefasciatus (Skalsky et al, 2010). Studies in Anopheles gambiae mosquitoes identified miR-10, miR-184, miR-281 and bantam as the most abundantly expressed miRNAs in adult females (Lampe and Levashina, 2018). In An.…”
Section: Aedes Aegypti Corpora Allata-corpora Cardiaca Mirna Repertoirementioning
confidence: 99%
“…In An. gambiae, the group of most abundant miRNAs changed before and after blood-feeding, and some of them dominated the repertoire only in specific tissues; for instance miR-281 in the midgut, miR-10 and miR-306 in the ovary and miR-8 and miR-276 in the head and fat body (Lampe and Levashina, 2018).…”
Section: Aedes Aegypti Corpora Allata-corpora Cardiaca Mirna Repertoirementioning
confidence: 99%
“…MicroRNAs (miRNAs) are small endogenous noncoding RNAs that regulate gene expression, primarily via RNA decay or posttranslational inhibition [8]. Most mosquito miRNA studies have concentrated on identification and annotation using high-throughput sequencing and subsequent bioinformatics analysis [9][10][11][12][13][14]. However, only a few miRNAs have been functionally studied in malaria mosquitoes [15,16] partly because of the lack of genome-wide resources for assessing loss of miRNA function.…”
Section: Introductionmentioning
confidence: 99%